Konsep Pendidikan dan Islam Sebagai Alternatif dalam Memanusiakan Manusia - Muhamad Turmuzi (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
Study of education and Islam is one of the obligations of mankind, especially for Muslims because education and Islam are two scientific disciplines in living life. Islam itself is present carrying teachings cover all human life, especially in terms of education, social, political and economic. This article description of education and Islam as an alternative to humans, namely how humans live in the world with their fellow humans, refer to foundation of Koran and Sunnah, especially for Muslims teachings that emphasize humans in Science. This paper aims to gather information about the concept of education and Islam as the best way for humans to live. In obtaining this information, this paper uses descriptive research methods or literature review with the process of utilizing relevant books and articles. Because in this modern era, whatever the problems faced by mankind by making education and Islam as a way (alternative) to humanize humans, all the problems of life will be easier to deal with and make life more prosperous.